2014
DOI: 10.1055/s-0034-1383132
|View full text |Cite
|
Sign up to set email alerts
|

Pertrochantäre Femurfraktur – eine Anfängeraufgabe?

Abstract: Internal fixation with nailing in pertrochanteric femur fractures is a standard operative approach. It is suitable as a "beginner's" procedure, that is quickly and easily performed. Only complex, multifragmented or markedly displaced or long-segment fractures need to be treated by staff physicians. Mortality is not affected by the surgeon's experience, but rather by comorbidity and from the preoperative duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Hip fractures are typical injuries of the elderly [1]. Recent studies prove that the incidence of these entities rises dramatically with increasing age [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hip fractures are typical injuries of the elderly [1]. Recent studies prove that the incidence of these entities rises dramatically with increasing age [1].…”
Section: Introductionmentioning
confidence: 99%
“…Hip fractures are typical injuries of the elderly [1]. Recent studies prove that the incidence of these entities rises dramatically with increasing age [1]. In 2008 Lohmann et al showed an incidence of 0.06 percent at an age between 60 and 64 years and an incidence of 1.3 percent at people at their eighties [2].…”
Section: Introductionmentioning
confidence: 99%